THERMOELECTRIC HEAT GENERATOR’S FUNCTIONING PRINCIPLE - Mamarasulov Qudratbek Shuxratbek o‘g‘li; Meliboev Azizbek Zoirjon o‘g‘li (Лучшие интеллектуальные исследования, 2024)
Abstract: This article explores the principle of operation of thermoelectric heat generators and their use in various aspects, as well as the useful and unprofitable aspects of this type of generators. In contrast to thermoelectric generators, the Seeback effect is also emphasized, because this type of generator is built on the same basis.